Impact of rapid microbial identification directly from positive blood cultures using matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry on patient management. (27th July 2013) - Martiny, D.; Debaugnies, F.; Gateff, D.; Gérard, M.; Aoun, M.; Martin, C.; Konopnicki, D.; Loizidou, A.; Georgala, A.; Hainaut, M.; Chantrenne, M.; Dediste, A.; et al.
Abstract For septic patients, delaying the initiation of antimicrobial therapy or choosing an inappropriate antibiotic can considerably worsen their prognosis. This study evaluated the impact of rapid microbial identification (RMI) from positive blood cultures on the management of patients with suspected sepsis. During a 6‐month period, RMI by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) was performed for all new episodes of bacteraemia. For each patient, the infectious disease specialist was contacted and questioned about his therapeutic decisions made based on the Gram staining and the RMI. This information was collected to evaluate the number of RMIs that led to a therapeutic change or to a modification of the patient's general management (e.g. fast removal of infected catheters). During the study period, 277 new episodes of bacteraemia were recorded. In 71.12% of the cases, MALDI‐TOF MS resulted in a successful RMI (197/277). For adult and paediatric patients, 13.38% (21/157) and 2.50% (1/40) of the RMIs, respectively, resulted in modification of the treatment regimen, according to the survey. In many other cases, the MALDI‐TOF MS was a helpful tool for infectious disease specialists because it confirmed suspected cases of contamination, especially in the paediatric population (15/40 RMIs, 37.50%), or suggested complementary diagnostic testing. This study emphasizes the benefits of RMI from positive blood cultures. Although the use of this technique represents an extra cost for the laboratory, RMI using MALDI‐TOF MS has been implemented in our daily practice.